Body mass index and brain structure in healthy children and adolescents. (1st January 2014) - Alosco, Michael L.; Stanek, Kelly M.; Galioto, Rachel; Korgaonkar, Mayuresh S.; Grieve, Stuart M.; Brickman, Adam M.; Spitznagel, Mary Beth; Gunstad, John
<x xml:space="preserve">Abstract</x> Obesity is associated with cognitive dysfunction in children and adolescents, although the mechanisms underlying these deficits remain unclear. This study examined the associations between body mass index (BMI) and regional gray matter volume and white matter integrity in 120 healthy children and adolescents (6–18 years of age) who underwent magnetic resonance and diffusion tensor imaging. Bonferroni-corrected partial correlation analyses controlling for demographic and clinical characteristics revealed significant inverse associations between demographically standardized BMI values and gray matter volume of frontal (r = −0.31) and limbic (r = −0.35) brain regions. No such pattern emerged for fractional anisotropy of white matter tracts. Subsequent hierarchical regression analyses indicated that the relationship between standardized BMI and structural gray and white matter brain indices did not vary with age. These findings suggest that obesity in children and adolescents is associated with decreased volume of frontal and limbic cerebral gray matter regions. Further research is much needed to better elucidate possible brain-based mechanisms for cognitive dysfunction associated with obesity.